Internationalization of Canadian higher education: discrepancies between policies and international student experiences. Issue 5 (4th May 2017) - Guo, Yan; Guo, Shibao
Abstract : The internationalization of higher education in Canada is happening at a rapid pace. One manifestation of internationalization is the increasing enrolment of international students in Canadian institutions. There is little research on international undergraduate students' experiences from their own perspectives as they adapt to a new educational system in Canada. This research examines how internationalization policies at a university in Western Canada were interpreted and experienced by international undergraduates. Based on interviews with 26 such students from 9 countries, this study shows that students have multiple understandings of internationalization and view internationalization as a positive experience for academic and personal growth. Findings also indicated several persistent problems, including a neoliberal approach that treats internationalization as a marketing strategy, limited internationalization of the curriculum, and gaps between the internationalization policy and the experience of international students. The findings have important implications for providing appropriate support for international students and for internationalization policy in higher education.